Ecotourism as an Alternative Therapeutic Space for Emotional Well-being in Contemporary Society - Poshakrishna, Pakaus; Khanto, Orathai; Chumsong, Kanjana; Taweewat, Natchaya (Journal of Dhamma for Life, 2026)
Mental health issues in humans have received more attention than ever before. Not only adults suffer from depression or burnout, but children and youth can also experience these conditions. Therefore, people seek safe spaces through various means, such as reading, shopping, and even traveling. Amidst the trend of ecotourism through camping and hiking, the use of natural sounds as a tool for healing the mind, such as the sound of rain, flowing water, and birds, are tools for healing the exhausted mind from the fast-paced pace of urban life, informed by the Healing Environment Theory. Furthermore, this article focuses on creating safe spaces through ecotourism using the Place Attachment Theory. This theory emphasizes the relationship between people and their spaces, creating meaning and safety within spaces, leading to favorite places and favorite parks. Revisiting these spaces repeatedly develops into safe spaces for personal healing.